2021
DOI: 10.1038/s41598-021-89782-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of bovine papillomavirus DNA by digital droplet PCR in sheep blood

Abstract: Highly pathogenic bovine papillomaviruses (BPVs) were detected and quantified for the first time using digital droplet polymerase chain reaction (ddPCR) by liquid biopsy in 103 clinically healthy sheep. Overall, ddPCR detected BPVs in 68 blood samples (66%). BPV infection by a single genotype was revealed in 61.8% of the blood samples, and BPV coinfection by double, triple or quadruple genotypes was observed in 38.2% of liquid biopsies. The BPV-2 genotype was most frequently seen in sheep, whereas BPV-1 was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The reaction was performed in a final volume of 22 μL, containing 11 μL of ddPCR Supermix 2x for Probes, 2 μL reverse transcriptase, 1 μL DTT and 1 μL of primer and probe mix for all 4 delta BPVs. The sequences of primers and probes used to verify the presence of the delta BPV transcripts were previously used ( 22 24 ). The plate was transferred to an automated droplet generator (AutoDG, Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was performed in a final volume of 22 μL, containing 11 μL of ddPCR Supermix 2x for Probes, 2 μL reverse transcriptase, 1 μL DTT and 1 μL of primer and probe mix for all 4 delta BPVs. The sequences of primers and probes used to verify the presence of the delta BPV transcripts were previously used ( 22 24 ). The plate was transferred to an automated droplet generator (AutoDG, Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…BPVs are typically responsible for latent infections. BPV DNA has been found to be highly prevalent in healthy cattle ( 22 ), as well as in small ruminants that were free at pasture ( 23 , 24 ). Establishment of a persistent BPV infection is a major risk factor for cancer development and requires the virus to evade the first line of defence the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, our study confirmed that ddPCR can be used for low-abundance nucleic acid detection and is very useful in diagnosing infectious diseases, including viral infections in comparative medicine (29). In addition, ddPCR is very accurate and sensitive diagnostic assay for the detection and quantification of human papillomavirus DNA (25,30,31) and BPV DNA (22)(23)(24).…”
Section: Discussionsupporting
confidence: 70%
“…In this context, our study confirmed that ddPCR can be used for low-abundance nucleic acid detection and is very useful in diagnosing infectious diseases, including viral infections in comparative medicine ( 29 ). In addition, ddPCR is very accurate and sensitive diagnostic assay for the detection and quantification of human papillomavirus DNA ( 25 , 30 , 31 ) and BPV DNA ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Droplet digital PCR (ddPCR) allows massive partitioning of DNA of the sample into millions of nanoliter-sized droplets that ideally contain either no particles or a single particle (21). Recently, ddPCR has been reported to detect and quantify bovine papillomaviruses BPVs in cattle, goats, and sheep (22)(23)(24). DdPCR has been shown to have higher accuracy than real-time quantitative PCR (qPCR).…”
Section: Introductionmentioning
confidence: 99%